Self-compassion and psychological well-being of radiographers at work - Leïla Jacquet; Marine Paucsik; Jean-Baptiste Guy; Karine Eve; Isabelle Ben-Taarit; Sophie Lantheaume (International Journal of Qualitative Studies on Health & Well-Being)
Objectives The aim of this study was to assess how self-compassion affects the psychological well-being of radiographers at work. Methods An online survey was sent to radiology and radiotherapy departments in Rhône-Alpes, a region of France (from October 2021 to February 2022). The study is mixed: quantitative data, with closed questions and two validated scales, and qualitative data, with open questions aimed at assessing perceptions among radiologists as regards self-compassion. Results A total of 253 radiographers (mean age 32.9 years), took part in this survey. Radiographers reported a poor level of well-being and a moderate level of self-compassion. We found a link between well-being at work and self-compassion. Gender, age, number of years of experience and the desire to receive training on well-being appear to have an impact on the level of self-compassion. The perception of self-compassion by radiologists is essentially positive. Conclusion Particular attention should be paid to radiologists who are female, young, and with only a few years of experience. Self-compassion is a protective factor for radiologists and may help them take care of themselves to continue caring for others. Training related to self-compassion should be promoted in medical imaging departments.